Neuropsychological in the Treatment of Academic Abilities of Children with Special Needs (Dysgraphia, Dyscalculia, Dyslexia, Slow learning) - Choirunnisa, Nadia; Mochamad Nursalim; Diana Rahmasari (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
This article describes research on the application of neuropsychological approaches in improving the academic abilities of children with special needs, including dysgraphia, dyscalculia, dyslexia, and slow learners. Using descriptive qualitative methods, this study describes in detail the impact of neuropsychological interventions on participants with learning difficulties. The results of the analysis showed significant improvements in these children's writing skills, math ability, reading skills, and learning comprehension speed. This study indicates that neuropsychological approaches can provide practical support in addressing the academic challenges of children with special needs by detailing the behavioral and cognitive changes observed during the intervention. The practical implication is that these methods can be integrated into educational programs tailored to meet individual needs, improving learning efficiency and effectiveness. In conclusion, this article contributes to our understanding of the positive potential of neuropsychological approaches in supporting the academic development of children with learning difficulties, paving the way for developing more adaptive intervention strategies focused on each child's specific needs.